SNAKES FROM THE PONTAL DO TRIÂNGULO MINEIRO REGION, CERRADO DOMAIN, SOUTHEASTERN BRAZIL - Siqueira, Lucas Henrique Carvalho; Facure, Kátia Gomes (Ciência e Natura, 2017)
Snakes play an important ecological role, interacting with other species and feeding on some that are considered pests and illness vectors. The present work aims to list the snake species present in the Municipality of Ituiutaba, southeastern Brazil. The data were obtained from preserved specimens deposited in zoological collections, visual surveys and occasional encounters. Fifty-seven individuals were analyzed, and we identified twenty-three species, distributed in five families. The number of species found is relatively high, considering the advanced degree of alterations in the natural environment, where only 15% remains intact. In our sample, we identified individuals of two viperid genera with medical and pharmacological importance. The present study contributes to the knowledge on snake assemblages in the Cerrado, and emphasizes the importance of inventories of the local fauna, mostly in environments with anthropic action, resulting in loss of habitats.